IN THE RESOLUTION OF EMERGENCY SITUATION’S ROLE OF ROBOTICAL EQUIPMENT (Web of Technology: Multidimensional Research Journal, 2025)
The research work briefly describes the level of effectiveness of remote-controlled robotic tools today. As a result of the research carried out within the framework of this research work, a model of a mobile robotic device with remote control, designed for emergency response and monitoring of the situation, was developed and studied as information for the purpose of making additions to it. Research and test results confirmed that the capabilities of the developed mobile robotics tool after modification differ from the initially established technical indicators for the better.